Pengaruh Bauran Promosi dan Brand Awareness terhadap Minat Beli Produk Makanan Ringan dalam Platform Tiktok dengan Mediasi Konten Kreatif pada Mahasiswa Program Studi Manajemen - Aulia Farrel El Amien (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the impact of promotional mix and brand awareness on the purchase intention of snack products on TikTok, with creative content as a mediating variable. Using an associative quantitative approach, data were collected through a survey of 222 Management students at Universitas Negeri Malang. The findings indicate that both the promotional mix and brand awareness positively and significantly influence creative content and purchase intention. Creative content serves as a significant mediator between independent variables (promotional mix and brand awareness) and the dependent variable (purchase intention). Statistically, the research model fulfills validity and reliability criteria, with R-Square values indicating moderate to strong relationships. This study offers implications for social media marketing strategies, particularly in optimizing creative content to enhance purchase intention among younger generations.